THE IMPACT OF EPS, DPS, BVS, AND ROA TOWARD STOCK PRICE - Linanjung, Yolanda Ardestya (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study is aimed to analyse the significantly impact of Earnings Per Share, Dividend Per Share, Book Value Per Share, and Return On Assets toward Stock Price of Publicily Listed Firms in Jakarta Islamic Index (JII) Period 2009-2013 not only simultaneously but also partially. This study uses secondary data from Indonesia Capital Market Directory (ICMD) of the firms, Annual Report of the firms, and financial report of the firms from 2009 to 2013. Population in this study is thirty firms which publicily listed firms in Jakarta Islamic Index in the period 2009-2013. Sample in this study is ten firms which are taken based on purposive sampling method. Data analysis model which is used in this study is Multiple Linear Regression with Panel Data. Hypothesis test which is used in this study are F Test, R2 Test, and t Test. The result of hypothesis test shows that Earnings Per Share, Dividend Per Share, Book Value Per Share, and Return On Assets simultaneously have positive significant impact toward Stock Price. The value of R2 is 97,5516 % so 97,5516 % of variable Stock Price can be teached by variable Earnings Per Share, Dividend Per Share, Book Value Per Share, and Return On Assets, while the residue 2,4484 % is teached by the other variables in the outside of this study. Earnings Per Share partially has positive significant impact toward Stock Price, while Dividend Per Share, Book Value Per Share, and Return On Assets partially doesn’t have positive significant impact toward Stock Price. Keywords: Stock Price, Earnings Per Share, Dividend Per Share, Book Value Per Share, and Return On Assets.